Model test study on surrounding rock deformation and failure mechanisms of deep roadways with thick top coal. (March 2015) - Li, S.C.; Wang, Q.; Wang, H.T.; Jiang, B.; Wang, D.C.; Zhang, B.; Li, Y.; Ruan, G.Q.
Graphical abstract: Highlights: A combined type large-scale geomechanical model test system applicable to deep roadways with thick top coal was developed. Model test typical deep roadway with thick top coal was conducted. The surrounding rock deformation and failure mechanisms of deep roadways with thick top coal were analyzed. The deformation and failure on the roof of the deep roadways with thick top coal are more serious. Abstract: The deep roadway with thick top coal is a typical roadway difficult to support in deep mining project, and resolving this sophisticated problem to control the stability of surrounding rock is of great significance in safety production of coal mines. In order to explore the surrounding rock deformation and failure mechanisms of such deep roadways, with Zhaolou coal mine in Juye mining area of China as the engineering background, a large-scale geomechanical model test was carried out. The displacement and stress evolution laws of surrounding rock supported by the pressure relief anchor box beam system were researched. Meanwhile, the related results validate and analyze main failure characteristics and mechanisms of the surrounding rock by comparing with field test.